The Influence of Information Technology, Human Resources Competency and Employee Engagement on Performance of Employees - Heslina, H.; Syahruni, Andi (Golden Ratio of Human Resource Management, 2021)
This study was conducted with the following objectives to analyze the influence of Information Technology, Human Resources (HR) and work engagement on performance of the Makassar Regional Revenue Agency employees. The research method used in this research is descriptive analysis and analysis of multiple linear regression, with a total sample of 142 respondents. Multiple regression analysis is the method used to answer the relationship between independent and dependent variables. After the regression coefficient is obtained, testing is carried out to determine the independent variables on the dependent variable using the Fisher's test, t-test, and the coefficient of determination.  Based on the multiple linear regression analysis results, the results showed that Information Technology, HR competence, and work Engagement have a positive and significant effect on the Performance of Regional Revenue Agency Employees of Makassar City, which can be proven from partial and simultaneous testing. With these results, all hypotheses in this study can be proven or accepted. The results of this study suggest that the information technology used must provide benefits and be supported by human resources who have the expertise to create a work climate that can support employee and organizational performance in Regional Revenue Agency Office of Makassar City